2013
DOI: 10.1186/1745-6215-14-209
|View full text |Cite
|
Sign up to set email alerts
|

Alexander Technique Lessons, Acupuncture Sessions or usual care for patients with chronic neck pain (ATLAS): study protocol for a randomised controlled trial

Abstract: BackgroundChronic neck pain is a common condition in the adult population. More research is needed to evaluate interventions aiming to facilitate beneficial long-term change. We propose to evaluate the effect of Alexander Technique lessons and acupuncture in a rigorously conducted pragmatic trial with an embedded qualitative study.Methods/DesignWe will recruit 500 patients who have been diagnosed with neck pain in primary care, who have continued to experience neck pain for at least three months with 28% minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Full details of the trial are published elsewhere [ 14 , 22 ]. Briefly, the ATLAS (Alexander Technique Lessons or Acupuncture Sessions) study was a pragmatic, multi-centre, three-armed RCT comparing acupuncture or Alexander lessons with usual GP care alone, for people with chronic, non-specific neck pain.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the trial are published elsewhere [ 14 , 22 ]. Briefly, the ATLAS (Alexander Technique Lessons or Acupuncture Sessions) study was a pragmatic, multi-centre, three-armed RCT comparing acupuncture or Alexander lessons with usual GP care alone, for people with chronic, non-specific neck pain.…”
Section: Methodsmentioning
confidence: 99%
“…We undertook a trial within a trial, that is, we nested the randomized trial of 'post-it notes' within the ATLAS trial, which is a large pragmatic randomized controlled trial of acupuncture or Alexander training or usual care for the treatment of neck pain [4]. The aim of this trial within a trial was to assess whether the use of a simple intervention, post-it notes, would result in a decrease in study attrition.…”
Section: Methodsmentioning
confidence: 99%
“…The earlier ATEAM trial demonstrated that, compared with usual care alone, one-to-one Alexander lessons led to significant long-term reduction in chronic or recurrent back pain and associated disability, [ 18 ]. ATLAS compared usual care alone with either Alexander lessons or acupuncture (both plus usual care) for primary care patients with chronic (median 6 years) non-specific neck pain [ [16] , [29] ]. The ATLAS trial clinical findings have already been reported, with the primary outcome of the Northwick Park Neck Pain Questionnaire demonstrating statistically significant and clinically meaningful reductions in pain and associated disability for both Alexander lessons and for acupuncture sessions compared with usual care alone, with the benefit maintained to at least 12 months [ 16 ].…”
Section: Introductionmentioning
confidence: 99%